Enhancing efficiency in construction scheduling for SMEs: A novel matrix-based VBA-excel model - L. Nguyen-Son; T. Thai-Phuong (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
Small and medium-sized enterprises (SMEs) in construction face challenges managing complex project schedules cost-effectively. This study develops a user-friendly, matrix-based VBA-Excel model to enhance scheduling efficiency. The objective is to create an accessible tool that automates task dependency management without requiring advanced coding skills. The model employs the Precedence Diagramming Method (PDM), integrating all dependency types (FS, SS, FF, SF) with lag/lead adjustments through VBA automation in Excel. Implementation involved designing a novel matrix structure for dependency handling and a simple interface, validated via case studies with 11 and 9 tasks, benchmarked against industry standards. Results show accurate schedule calculations matching benchmarks, with seamless adjustments, though processing slows for large projects. The tool enables SMEs to optimize resources, reduce delays, and improve competitiveness at no cost. Limitations include Excel’s computational limits and omission of real-world calendar constraints like holidays. Future enhancements could include cloud-based scalability and risk integration. This innovative model fosters inclusive project management, reducing infrastructure disparities in underserved regions.